الأدوار السياسية للإذاعات المحلية في الجزائر ــ دراسة حالة إذاعة الجزائر من الوادي ــ - فرج, عبد الحميد; مسعودي, زكرياء; معمر, حقيضة (جامعة الوادي - University of Eloued, 2022)
يقوم الإعلام العمومي الوطني بمواكبة العديد من الأحداث والمحطات السياسية التي تمر بها الجزائر ن حيث تخصص العديد من الحصص والومضات الإخبارية والاشهارية لذات الغرض .. ومن بين أهم وسائل الإعلام العمومي التي تعتمد عليها السلطة في صناعة الرأي العام ، والعمل على التنشئة السياسية للمواطنين ، وزيادة الوعي لهم نجد المحطات الإذاعية المحلية ومنها إذاعة الجزائر من الوادي ، كأحد أهم المحطات الإذاعية على المستوى الوطني .. حيث تتمايز المساحات الزمنية المخصصة للشأن السياسي حسب تواتر الأحداث السياسية على المستوى الوطني (انتخابات ، تغير سياسي ، حدث سياسي بارز ، خطاب لرئيس الجمهورية ... ) ، بينما تتقلص هذه المساحة في سائر أيام السنة، لتصل أحيانا الى برنامج واحد أسبوعي، وهو ما دأبت عليه إذاعة الجزائر من الوادي من خلال حصة وقفات، وهو الحيز الذي تلعب من خلاله إذاعة الوادي دورا هاما في مواكبة الأحداث الوطنية خاصة ، باستضافة أساتذة ومحللين سياسيين ، لتدارس المشهد السياسي وتنوير الرأي العام بأهم خلفيات وأبعاد هذه التطورات مع أنه تبقى أهم ما يميز هذه المساحات التي تتناول الشأن السياسي هو بقاؤها ضمن دائرة التوجيه الإعلامي، على اعتبار انها مؤسسة عمومية وليست خاصة، وبالتالي فإنه تنطبق عليها نظرية حارس البوابة في تناول القضايا السياسية، بالإضافة إلى نظرية الأولويات، على أساس أن القضايا السياسية ليست من أولويات الإذاعات المحلية. ABTRUCT: The national public media keeps abreast of many political events and stations that Algeria is going through, where it allocates many quotas and news flashes and advertisements for the same purpose. To them we find local radio stations, including Radio Algeria from the valley, as one of the most important radio stations at the national level .. Where the time allocated to political affairs is different according to the frequency of political events at the national level (elections, political change, a prominent political event, a speech to the President of the Republic ...), while this area shrinks throughout the year, sometimes reaching one weekly program, which is what Radio Algeria from the valley through the share of pauses, a space through which the radio plays an important role in keeping up with the national events, especially by hosting professors and political analysts, to study the political scene and enlighten the public opinion on the most important backgrounds and dimensions of these developments Although the most important characteristic of these areas dealing with political affairs is the fact that they remain within the Department of Media Guidance, as it is a public institution and not a private, and therefore it applies the theory of the gatekeeper in dealing with political issues, in addition to the theory of priorities, on the basis that political issues are not One of the priorities of local radio stations.
مقال
Keywords: إذاعة محلية ، إذاعة الجزائر من الوادي ، نظرية حارس البوابة ، أدوار سياسية ، نظرية ترتيب الأولويات; Local radio, Algeria radio from the valley, Political stations, Gatekeeper theory, Priority theory.